The Concept Of Nazm by Al-Jurjani As A Mature Rhetoric Theoretical Framework Applicable to The Analysis Of Arabic Texts/ فكرة النظم عند الجرجاني بوصفها نظرية بلاغية ناضجة قابلة للتطبيق في تحليل النصوص العربية - Muhammad Nur Afiq Aiman Md. Noraffendie; Mohd Shahrizal Nasir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines a rhetorical perspective in Arabic rhetoric associated with ʿAbd al-Qāhir al-Jurjānī, namely the concept of nazm, as a tool to discover the secrets of Arabic rhetoric, especially in the Qur’an. To maximize scholarly benefit, the study aims to determine the status of this concept and to demonstrate the extent of its methodological maturity and its capacity to function as a theoretical framework for understanding Arabic texts for rhetorical analysis. To achieve these aims, the researcher adopts a qualitative descriptive–comparative approach. In practice, the study collects relevant materials from primary and secondary sources, such as journal articles and postgraduate theses. Then it proceeds with procedural steps that include classifying the materials, compiling key statements, and comparing them to identify the locus of methodological distinctiveness in ʿAbd al-Qāhir al-Jurjānī’s conceptualization. The findings show that ʿAbd al-Qāhir al-Jurjānī offers a distinctive concept by shifting rhetorical inquiry from a focus on subjective word ordering to an integrated interpretive construction that links wording and meaning through “the interrelation of words” (taʿlīq al-kalim) and the principle of “seeking the meanings of grammar” (tawakhkhī maʿānī al-naḥw). Historically, the development of the concept of nazm moved from a predominantly sensory, lexical concern to a formulation that integrates wording, meaning, and context, culminating in ʿAbd al-Qāhir al-Jurjānī’s work, where it effectively transitions from a mere idea into a mature rhetorical theory suitable for applied analysis. In addition, exegetical and rhetorical evidence indicate that Nazm is highly applicable to the analysis of Arabic texts, as it has become an effective tool for revealing their rhetorical secrets. Accordingly, the study concludes that the concept of nazm represents a mature rhetorical vision that can serve as a methodological framework for understanding the subtleties of Arabic discourse and extracting its rhetorical insights in the Qur’an and beyond